(untitled) - Hillel, Daniel (Burlington, MA, 2007)
This text offers an encompassing perspective regarding the soil's impact on the environment by organizing chapters among the three main sets of interacting processes: Physical, and biological.
Keywords: Đất đai,Soils; Khía cạnh môi trường,Environmental aspects